Borocarbonitride, (BN)x(C)1-x, nanosheet-reinforced polymer nanocomposites for high mechanical performance - Sreedhara, M.B. (2020)
The enhancement in mechanical and thermal properties of polymer matrices upon reinforcing with nanoparticles strongly depends on the extent of molecular-level interactions and interfacial adhesion between the nanofiller and the matrix material, which are, in turn, governed by the surface functionalities on the nanofiller. Herein, we examine the reinforcing effect of nanosheets of borocarbonitide, (BN)x(C)1-x, which are analogues to graphene (x = 0) and boron nitride sheets (x = 1), whose surface functional groups vary with the composition, on the mechanical and thermal properties of poly(vinyl alcohol), PVA. Results show that substantial improvement in hardness and elastic modulus of PVA is achieved by adding just 0.2 wt% of BCN. A significant enhancement in the thermal stability was also noted. These results are rationalized by recourse to detailed structural characterization, which shows a substantial enhancement in the degree of crystallinity in PVA upon BCN addition, and improved interfacial adhesion between the nanofiller and the polymer matrix via strong intermolecular interactions. Overall, our results show that it is possible to engineer polymer matrix nanocomposites with exceptional mechanical and thermal properties via the addition of a small amount of BCN.